Exergetic analysis of a dual-fuel engine, PEM electrolyzer and thermoelectric generator integrated system (2019)
In this research, the implementation of an integrated system composed of a dual-fuel engine (Diesel-Hydrogen), a PEM electrolyzer and a thermoelectric generator is envisioned. In order to know the optimal operating conditions of each sub-system, the exergetic efficiency and destroyed exergy were studied. It was estimated that for the dual combustion engine, the destroyed exergy would increase as a function of the concentration of methane in its mixture. By varying the electrical input to the electrolyzer, it was found that when the input current was 2A, the exergetic efficiency would go up to 92.59%, while for a current of 5A, the efficiency decreased in 51.80%. Finally, the exergetic efficiency of TEG decreased by increasing the hot flow temperature; 86.68% of the decrease in efficiency occurred for temperatures between 470K and 510K. On the other hand, the destroyed exergy increased linearly with an increase in the inlet temperature of exhaust gases.